FIXING THE DECLINING FOUNDATIONS - SPECTRUM AND MANAGEMENT OF PEDIATRIC AND ADOLESCENT HEALTH - ZEB, L; ZEB, S; MEHMOOD, Z (Biological and Clinical Sciences Research Journal, 2023)
This medical research study will follow a cohort of 100 individuals for an entire year to evaluate the range and management of pediatric and adolescent health concerns. The study aims to comprehend the prevalence of a-etiology, clinical presentation, and therapy of prevalent pediatric and adolescent health disorders. This study aims to enhance children’s and adolescents’ general healthcare outcomes and well-being by analyzing data gathered through various clinical and diagnostic techniques. A Prospective Cohort Study was conducted at the Department of Obs & Gynae, MTI LRH, Peshawar, from Jan 2022 to Jan 2023 With 100 patients aged 0 to 18, this study used a prospective cohort design to examine children’s and adolescents’ health over a year. A wide range of healthcare facilities within a particular urban area were used to enroll patients, resulting in a representative sample. Numerous data points were collected, including demographic data, medical histories, physical and mental health evaluations, socioeconomic level, and parental engagement. Interventions and techniques for health management were also documented. While qualitative data underwent thematic coding, quantitative data were analyzed using statistical software. Informed consent was acquired after ethical issues were addressed. This approach sought to thoroughly grasp pediatric and adolescent health problems and how to treat them. Physical health problems predominated among the 100 pediatric and teenage patients investigated over one year, with infections (23%), chronic diseases (15%), and injuries (18%) standing out. There were considerable mental health problems, with 26% exhibiting symptoms of depression and 18% exhibiting anxiety symptoms. Socioeconomic characteristics, such as income and education levels, influence health outcomes. A multidisciplinary approach, preventive programs, and increased accessibility to healthcare effectively managed these problems. Finally, the multidimensional nature of health issues in this demographic was underscored by our one-year study on 100 pediatric and teenage patients. Early intervention and comprehensive care were required for physical and mental health issues, frequently influenced by socioeconomic conditions. To successfully address these issues, a multidisciplinary approach, preventative initiatives, and improved access to healthcare have become essential methods.